Peran Ibu Rumah Tangga Dalam Meningkatkan Pendapatan Keluarga Melalui Pembuatan Emping Melinjo Rumahan (Studi Kasus Di Desa Padang Birik-Birik Kecamatan Pariaman Utara) - Rahmayanti, Yesi; Murni, Yanti; Mulyani, Sri (LPPM Universitas Dharma Andalas, 2024)
This study aims to determine the role of housewives in increasing family income through making home-made melinjo chips. The data in this study were collected through interviews with 10 housewives in Padang Birik-Birik Village, North Pariaman District. The data analysis technique used descriptive analysis and SWOT analysis. The results showed that the internal factors that influenced the development of the melinjo emping-making business in Padang Birik-Birik were the delicious taste of the chips, the long-standing business, dependence on raw materials and the absence of promotion. Meanwhile, external factors include many events that use melinjo chips, tight competition and fluctuating raw material prices. The role of housewives is very influential in family income and helps husbands in meeting the needs of daily life. Factors that support housewives in increasing family income through the manufacture of melinjo chips such as raw materials that are easy to obtain because the melinjo tree is around the place of residence, the time of making melinjo chips, consumer demand and creating jobs for the community around Padang Birik-Birik Village and factors that hindering housewives in increasing family incomethrough the manufacture of melinjo chips such as limited capital, product marketing problems and the uncertain availability of raw materials because there are some housewives who do not have melinjo trees